Analysis flow of second order fluid in a vertical channel with porous wall by using the Homotopy Analysis Method (HAM) - Wala’a Abdul; Mageed Mahdi; Ahmed M. A. Hadi (Journal of Madenat Alelem University College, 2015)
In this paper, the state of non newtonian fluid of second order flow injected uniformly into the vertical channel with porous wall through one side of the channel. The equations which are used to describe the flow are the motion and the energy equations. It found that these equations are controlled by many dimensionless numbers such as Reynolds number (Re), Peclet number (Pe), Hartman number (M) and the material of fluid (α,β). The homotopy analysis method (HAM) is used to obtain the analytic solution for the velocity and heat transfer. The effect of each dimensionless parameters upon the velocity and temperature distribution is analyzed and shown graphically by using MATLAB package.